PERILAKU IMPULSIVE BUYING MELALUI LIVE STREAMING DAN FLASH SALE PENGGUNA E-COMMERCE - Irvan Rolyesh Situmorang (Smart Education, 2025)
Abstract: The aim of this research is to determine the partial and simultaneous influence of the use of live streaming and flash sales on the impulsive buying behavior of e-commerce users in the East Siantar sub-district. This research uses quantitative research with a Likert scale as a measuring tool. The population in this study cannot be known with certainty so sampling was carried out using the Hair formula. The Hair formula is calculated by multiplying the number of indicators for each variable by 10. The results of the first hypothesis show that live streaming partially has a positive and significant effect on impulsive buying behavior in the East Siantar sub-district. The second hypothesis shows that flash sales partially have a positive and significant effect on impulsive buying behavior in East Siantar sub-district. The third hypothesis shows that live streaming and flash sales simultaneously have a positive and significant effect on impulsive buying behavior in the East Siantar sub-district. The results of the coefficient of determination show that the contribution of live streaming and flash sales has a value of 30% while the remaining 70% is influenced by other factors not included in this researchÂ Keywords: Live Streaming; Flash Sale; Impulsive Buying. Abstrak: Tujuan dilakukan penelitian ini adalah untuk mengetahui pengaruh secara parsial dan simultan penggunaan live streaming dan flash sale terhadap perilaku impulsive buying pengguna e-commerce di kelurahan Siantar Timur. Penelitian ini menggunakan penelitian kuantitatif dengan skala likert sebagai alat ukurnya. Populasi dalam penelitian ini tidak dapat diketahui secara pasti sehingga pengambilan sampel yang dilakukan menggunakan rumus Hair. Rumus Hair dihitung dengan cara jumlah indikator setiap variabel dikali dengan 10. Adapun hasil hipotesis pertama menunjukkan bahwa live Streaming secara parsial berpengaruh positif dan signifikan terhadap perilaku impulsive buying di kelurahan Siantar Timur.Â hipotesis kedua menunjukkan bahwa flash sale secara parsial berpengaruh positif dan signifikan terhadap perilaku impulsive buying di kelurahan Siantar Timur. hipotesis ketiga menunjukkan bahwa live Streaming dan flash sale secara simultan berpengaruh positif dan signifikan terhadap perilaku impulsive buying di kelurahan Siantar Timur. Hasil koefisien determinasi menunjukkan hasil bahwa kontribusi live streaming dan flash sale memiliki nilai sebesar 30% sedangkan 70% sisanya dipengaruhi faktor lain yang tidak termasuk dalam penelitian iniÂ Kata kunci: Live Streaming; Flash Sale; Impulsive Buying.